Latest advances in management of small cell lung cancer and other neuroendocrine tumors of the lung. (2020) - Assi, Hussein A.; Padda, Sukhmani K.
Highlights: Neuroendocrine tumors of the lung are a diverse group of diseases. Small and large cell neuroendocrine carcinomas are high-grade tumors with poor prognosis. Identification of novel targetable pathways has led to potential therapeutic options. Immunotherapy in combination with chemotherapy is the new frontline treatment in SCLC. LCNEC represents a heterogeneous disease with lack of robust data for management. Abstract: Neuroendocrine tumors of the lung are a diverse group of diseases with distinct pathological, molecular, and clinical characteristics. The most recent World Health Organization (WHO) classification identifies two types of high-grade neuroendocrine carcinomas of the lung: small cell lung carcinoma (SCLC), and the less common large cell neuroendocrine carcinoma of the lung (LCNEC). Systemic treatments for these aggressive tumors have largely remained unchanged for years. With the advancement in genomic sequencing and identification of novel targetable pathways over the last decade, a myriad of therapeutic options have emerged, addressing unmet needs for this patient population. In this review, we summarize the latest advances in the management of SCLC and LCNEC, and discuss promising endeavors in development.